The Effect of Creativity on Entrepreneurial Motivation - Reni Respita (Jurnal Ilmiah Pendidikan Scholastic, 2020)
The purpose of this study was to determine the effect of creativity on entrepreneurial motivation in students of the Faculty of Economics, State University of Padang. The population in this study were 1,209 students. The sampling technique used was proportional random sampling in order to obtain a sample of 300 students. The research instrument used was a questionnaire. Data analysis in this study using simple regression analysis. The results of this study indicate that creativity has a significant and positive effect on student entrepreneurial motivation.